Market structure and cost pass-through in retail - Gee Hee Hong; Nicholas Li (Bank of Canada, 2013)
We examine the extent to which vertical and horizontal market structure can together explain incomplete retail pass-through. To answer this question, we use scanner data from a large U.S. retailer to estimate product level pass-through for three different vertical structures: national brands, private label goods not manufactured by the retailer and private label goods manufactured by the retailer. Our findings emphasize that accounting for the interaction of vertical and horizontal structure is important in understanding how market structure affects pass-through, as a reduction in doublemarginalization can raise pass-through directly but can also reduce it indirectly by increasing market share.
Keywords: E30; E31; L11; L16; 330; Inflation and prices; Transmission of monetary policy